Variable precipitation climate risk as to the state of Tamaulipas - Aguirre-Bortoni, Manuel de Jesús (Universidad Autónoma de Tamaulipas, 2011)
The temporal variability of rainfall affects many human activities, especially in the handling and management of water resources, prevention of floods and droughts, planning and operation of agriculture, hydropower generation and water supply to the population human. The objective was to generate the mapping of rainfall to Tamaulipas, which were used for 140 meteorological stations, which are geographically located using GPS technology. We captured information Torrential Rains (Maximum in 24 hours) in digital format files. For processing and analysis of geographic data is created an image grid (raster) to a specific area per pixel (1 km2), based on the coverage of weather stations and study area of the project. In the creation of thematic mapping, we used the method of Universal Kriging spatial interpolation. The potential danger of heavy rainfall are found for the interval 230.7 to 580.0 mm, which is located to the towns of the Gulf Coast of Mexico, Soto la Marina and Aldama. Furthermore, the portion located in the South such as Ocampo, Xicoténcatl, Old Morelos, Nuevo Morelos y Gómez Farías.